Case report: Rare Guillain-Barré syndrome variants and mild encephalitis/encephalopathy with a reversible splenial lesion as the para-infectious manifestations of SARS-CoV-2 infection - Si, Wei; Li, Yuanrui; Du, Ganqin (Frontiers in Immunology, 2024)
Background: The Coronavirus disease 19 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a threat to human health. Although the COVID-19 pandemic is finished, some peoples are still suffering from this disease. Herein, we report the first case of SARS-CoV-2-associated Guillain-Barré syndrome (GBS) presenting as polyneuritis cranialis (PNC) and acute panautonomic neuropathy (APN) variants, accompanied by mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) and hyponatremia. Case presentation: A 32-year-old female patient with symptoms indicating multiple cranial nerve involvement, as well as sympathetic and parasympathetic nervous system dysfunction, was diagnosed as SARS-CoV-2-associated GBS presenting as PNC and APN variants, accompanied by MERS and hyponatremia. Following treatment with immunoglobulin, methylprednisolone, and symptomatic care, the patient’s inflammatory cytokines and serum sodium became normal. However, some residual symptoms such as postural hypotension, fatigue, and mild dysarthria persisted at the 9-month follow-up. Conclusion: This case highlights the unique presentation of SARS-CoV-2 infection. The involvement of both the central nervous system (CNS) and the peripheral nervous system (PNS) in this case underscores the complex neurological manifestations of COVID-19. Although the exact underlying pathogenesis of this case is unclear, inflammatory cytokines, particularly IL-6, may be implicated. Further research is needed to better understand the mechanisms underlying these complications and to optimize treatment strategies for affected patients.